The contemporary retreat of Tasman Glacier, Southern Alps, New Zealand, and the evolution of Tasman proglacial Lake since AD 2000 - Dykes, Robert C.; Brook, Martin S.; Winkler, Stefan (ERDKUNDE, 2010)
The Tasman Glacier is one of many freshwater-terminating glaciers located in the Aoraki/Mt Cook National Park that has retreated significantly since the mid-20th century. Although there have been several observations made of the glacier since the formation of Tasman Lake and the following rapid retreat, the glacier entered a period of rapid terminus disintegration and retreat since c. AD 2000. The retreat of Tasman Glacier between 2000 and 2008 has occurred in two distinct periods: an initial period of relatively slow retreat prior to 2006, followed by a secondary period of rapid retreat between 2006 and 2008. Terminus full width retreat for the period 2000–2006 occurred at a rate of 54 m a-1, accelerating to 144 m a-1 during 2006–2008. During the period 2000–2006, the controlling process of ice loss at the terminus was iceberg calving resulting from thermal undercutting. In contrast, the retreat between 2006 and 2008 was probably controlled by buoyancy-driven iceberg calving caused by decreased overburden pressure as a result of supraglacial pond growth. As a result, the surface area of Tasman Lake has increased by 86% over the period 2000–2008, with lake volume increasing by 284% between 1995 and 2008. Currently, the volume of Tasman Lake is 510 × 106 m3. It will increase dramatically in near future as the lake expands into deeper water.